Jumps and Post-FOMC Announcement Returns in Currency Markets - Lee, Suzanne S; Wang, Minho (The Review of Asset Pricing Studies, 2025)
Abstract We investigate intraday return dynamics in currency markets around FOMC announcements. Using comprehensive high-frequency exchange rate data, we reveal that post-FOMC announcement returns are significantly low, cancelling out approximately 65% of positive pre-FOMC announcement drifts. These post-announcement reversals mainly result from uncertainty resolution and are mostly realized between 12 and 24 hours after FOMC announcements. This return behavior is significantly related to the negative jump volatilities driven by FOMC announcements. Our findings suggest that our signed jump volatility measures capture informational shocks and uncertainty resolutions and tend to be high under illiquid market conditions. (JEL G14, G15)